Flame Retardancy Properties and Rheological Behavior of PP/DiDOPO Conjugated Flame Retardant Composites - Zhang, Daohai; Shang, Xiaoyu; Luo, Jiyong; Sun, Junzhuo; Tan, Fang; Bao, Dongmei; Qin, Shuhao (Frontiers in Chemistry, 2022)
A bridged 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative (DiDOPO) with conjugated structure was utilized as a novel conjugated flame retardant, Polypropylene(PP)/DiDOPO conjugated flame retardant composites were papered by being melt-extruding with a twin-screw extruder. The flame retardant efficiency of PP/DiDOPO conjugated flame retardant composites were investigated by cone calorimetry, limiting oxygen index (LOI), vertical burning test (UL-94). Besides, the rheological behavior of PP/DiDOPO conjugated flame retardant composites are measured by ARES rheometer. The results showed that when the content of DiDOPO with conjugated structure was 16 wt%, the LOI values of PP/DiDOPO conjugated flame retardant composites was 24%, and PP/DiDOPO conjugated flame retardant composites reaches V-0 grade. The heat release rate (HRR), total heat release rate (THR) and CO2 of PP/DiDOPO conjugated flame retardant composites decreased, so PP/DiDOPO conjugated flame retardant composites had excellent flame retardant effect. Rheological analysis results indicated that DiDOPO with conjugated structure suppressed the melt dripping of PP/DiDOPO conjugated flame retardant composites by enhancing the melt stability. The results showed that the DiDOPO with conjugated structure can significantly enhance the flame retardancy effect of PP/DiDOPO conjugated flame retardant composites. In addition, the materials PP/DiDOPO might be with low conductivity and charge transport mobility.